2020
DOI: 10.1038/s41467-019-14278-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying electron-transfer in liquid-solid contact electrification and the formation of electric double-layer

Abstract: Contact electrification (CE) has been known for more than 2600 years but the nature of charge carriers and their transfer mechanisms still remain poorly understood, especially for the cases of liquid-solid CE. Here, we study the CE between liquids and solids and investigate the decay of CE charges on the solid surfaces after liquid-solid CE at different thermal conditions. The contribution of electron transfer is distinguished from that of ion transfer on the charged surfaces by using the theory of electron th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
396
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 423 publications
(407 citation statements)
references
References 33 publications
10
396
0
1
Order By: Relevance
“…As for working mechanism, it mainly depends on the coupling effect of triboelectrification and electrostatic induction. [ 38–41 ] As shown in Figure 2e, when a force is applied, the two triboelectric layers come into contact with each other, resulting in the transfer of free electrons between the surfaces of the two triboelectric layers to a potential well. As the distance between the two triboelectric layers increases, a smaller barrier is formed and electrons remain moving between the surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…As for working mechanism, it mainly depends on the coupling effect of triboelectrification and electrostatic induction. [ 38–41 ] As shown in Figure 2e, when a force is applied, the two triboelectric layers come into contact with each other, resulting in the transfer of free electrons between the surfaces of the two triboelectric layers to a potential well. As the distance between the two triboelectric layers increases, a smaller barrier is formed and electrons remain moving between the surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…The results of our recent studies suggested an explanation for the divergence between intra and extracellular PN-OP and indicated that calcium ions are essential for intracellular PN-OP tension. Calcium ions and PN synergistically modulate the tension effect of PN-OP according the double electric layer theory [46,47] . Data from the present study also indicate that PN-OP elicited by BBB lesion factors is accompanied by an increase in calcium ions.…”
Section: Discussionmentioning
confidence: 99%
“…It is revealed that there are both electron transfer and ion transfer in the liquid-solid CE, where electron transfer plays a dominant role in liquid-solid CE [108]. Specifically, the CE between hydrophilic surfaces and aqueous solutions is likely dominated by ion transfer, while the CE between hydrophobic surfaces and aqueous solutions is more likely to be dominated by electron transfer [109].…”
Section: Summary and Perspectivesmentioning
confidence: 99%